2009
DOI: 10.1111/j.1365-2923.2009.03518.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated testing improves long-term retention relative to repeated study: a randomised controlled trial

Abstract: Repeated testing with feedback appears to result in significantly greater long-term retention of information taught in a didactic conference than repeated, spaced study. Testing should be considered for its potential impact on learning and not only as an assessment device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
243
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(258 citation statements)
references
References 13 publications
5
243
0
10
Order By: Relevance
“…Despite its limitations, the progress test, in addition to providing managers of courses with evidence for curricula decision-making, the test also provides valuable individual feedback, thus enhancing student learning. Some studies demonstrated that repeated testing with feedback appears to result, for the student, in greater retention of long-term knowledge, and thus, they suggested that Progress testing should be considered important not only as an evaluation tool but also as a powerful learning tool 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite its limitations, the progress test, in addition to providing managers of courses with evidence for curricula decision-making, the test also provides valuable individual feedback, thus enhancing student learning. Some studies demonstrated that repeated testing with feedback appears to result, for the student, in greater retention of long-term knowledge, and thus, they suggested that Progress testing should be considered important not only as an evaluation tool but also as a powerful learning tool 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The frequent testing model (the "testing effect") has demonstrated that repeated testing improves students' long-term recollection better than repeated studying. 6 The restructured laboratory activities implemented this type of testing model, in which students were tested, evaluated, and assessed each week.…”
Section: Designmentioning
confidence: 99%
“…First, there is no consensus about how much knowledge students have lost when they enter the clinical clerkships. Second, if knowledge deficit is a problem, then one way to address this is by frequent rehearsal and repeated testing during the retention interval, when students are attending courses on different subjects [20,21].…”
Section: Introductionmentioning
confidence: 99%